2022
DOI: 10.1001/jamaoto.2021.3228
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tumor Site With the Prognosis and Immunogenomic Landscape of Human Papillomavirus–Related Head and Neck and Cervical Cancers

Abstract: IMPORTANCE Human papillomavirus (HPV)-positive status in patients with oropharyngeal squamous cell carcinoma (OPSCC) is associated with improved survival compared with HPV-negative status. However, it remains controversial whether HPV is associated with improved survival among patients with nonoropharyngeal and cervical squamous cell tumors. OBJECTIVE To investigate differences in the immunogenomic landscapes of HPV-associated tumors across anatomical sites (the head and neck and the cervix) and their associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…To date, there have also been no reports of SR in human papillomavirus‐positive oropharyngeal squamous cell carcinomas (OPSCCs). By contrast, spontaneous regression in high grade‐cervical dysplasias which are HPV positive is well described and occurs in ~28% of cases 7 . To the best of our knowledge, this is the first report of spontaneous regression in an HPV‐positive OPSCC.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…To date, there have also been no reports of SR in human papillomavirus‐positive oropharyngeal squamous cell carcinomas (OPSCCs). By contrast, spontaneous regression in high grade‐cervical dysplasias which are HPV positive is well described and occurs in ~28% of cases 7 . To the best of our knowledge, this is the first report of spontaneous regression in an HPV‐positive OPSCC.…”
Section: Introductionmentioning
confidence: 76%
“…[12][13][14] It has also been indicated that immune checkpoint receptor such as PD-1 and TIGIT are upregulated in HPV-positive OPSCCs. 7 Among reports of SR, there also appears to be a higher incidence in tumors that are known to respond well to immunotherapy, such as renal cell carcinoma and melanomas. 2 Overall these findings corroborate the suspicion of an immune-activated environment in HPV-positive cancers and further the immunologic basis of tumor regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of cervical cancer, the effects of HPV on prognosis are also controversial, but this has been challenging to investigate because most cervical cancer cases are associated with HPV. 6 In this issue of JAMA Otolaryngology-Head & Neck Surgery, Zhu and colleagues 7 hypothesized that these differences in the biology and behavior of HPV-related tumors may be associated with the specific immune microenvironment found within the lymphoid tissue of the oropharynx. The tumor immune microenvironment plays a major role in shaping the genomic characteristics of the tumor.…”
mentioning
confidence: 99%
“…In this way, the tumor cells and immune cells are engaged in a constant game of cat and mouse. Zhu et al 7 hypothesized that a distinct immunophenotype is seen exclusively in HPV-related tumors of the oropharynx, possibly accounting for the well-established superior prognosis of these tumors vs HPV-negative HNSCC. 7 To explore this possibility, the authors analyzed genomic and transcriptomic data from the Cancer Genome Atlas, including data from 79 cases of OPSCC and 435 cases of nonoropharyngeal HNSCC.…”
mentioning
confidence: 99%